Analysis of Mental and Physical Fatigue Risk Factors in Utility Unit of Petrochemical Company - Bian Shabri Putri Irwanto (Universitas Airlangga, 2020)
Introduction: Work exhaustion defined as a tired feeling felt by workers with different symptoms in each individual. In this study work fatigue was divided into two types, namely physical work fatigue and mental work fatigue. This study aims to determine risk factors of physical and mental fatigue on utility unit PT. Trans Pacific Petrochemical Indotama (TPPI) which produces petroleum or gas, as well as the chemical BTX. Methods: This research was an observational study with a cross-sectional method. Based on the problem characteristic and data analysis, this study belongs to analytical research. Data were collected by interview, questionnaires, measurement, and observations. The population is 36 workers and the sample size of this study is 33 respondents from utility unit workers. The sampling technique used simple random sampling. The variables in this study were age, years of service, work duration, workload, heat stress index, responsibility, and support from company’s head. Results: Showed that factors associated with physical and mental fatigue are the age, workloads, work duration, and heat stress index. Conclusion: Physical fatigue and mental fatigue had correlation with age, workloads, work time, and heat stress index. The higher age, workload, work duration, and heat stress index, it will increasingly cause physical and mental fatigue faster and harder.Keywords: fatigue risk factors, mental fatigue work, physical fatigue work